Development of Fermented Mare’s Milk Using Mixed Probiotic Cultures - Tridjoko Wisnu Murti; Eni Robiyati; H. L. Jundi; F. Ramadhani; B. Rustamadji; Y. Y. Suranindyah (Faculty of Animal Science, Bogor Agricultural University, 2016)
Mare’s milk has good nutrient composition for human being in the form of natural milk or milk products. It can be used to replace cow’s milk, especially in the regions outside of Java Island which are rarely found dairy cow. This study had an objective to develop fermented mare’s milk by using mixed cultures of probiotic bacteria i.e. Lactobacillus acidophilus (A), Bifidobacterium longum (B), and Lactobacillus casei (C). The cultures of two probiotic bacteria AB and BC had been developed as well as three probiotic bacteria ABC culture. The mixed cultures (AB, BC and ABC) were prepared in single culture then cultivated in mixed culture as total 10% v/v of mare’s milk used and was incubated at 39°C for 9 h. The pH, acidity and bacterial count, each of them was analyzed in every 3 h of incubation time, while the organic acid and sensory tests were conducted at the end of 9 h of incubation. The results showed that the growth of mixed probiotic bacteria culture BC and ABC had better pH value that was around 3 compared with AB around 4.5. This showed that the cooperation between bacteria was different in each different combinations. The number of bacteria also increased sharply between 3-6 h of incubation time and 6-9 incubation time (AB and BC) along with the increased lactic acid, but the acetic acid decreased from 1750 mg/L to 1500 mg/L. The result of sensory test showed low acceptability of trained panelists. It is concluded that mixed cultures, using two or three probiotic bacteria (L. acidophilus, B. longum, and L. casei) could grow in mare’s milk. The change of the biochemical patterns indicated a commensalism cooperation among bacteria used. It was therefore the fermented mare’s milk using these probiotic bacteria were not well accepted by entrained panelists.